Global Health Risks : Mortality and Burden of Disease Attributable to Selected Major Risks. - Organization, World Health (World Health Organization, 2009)
Abbreviations; 1 Introduction; 1.1Purpose of this report; 1.2Understanding the nature of health risks; 1.3The risk transition; Figure 1: The causal chain. Major causes of ischaemic heart disease are shown. Arrows indicate some (but not all) of the pathways by which these causes interact.; ; Figure 2: The risk transition. Over time, major risks to health shift from traditional risks (e.g. inadequate nutrition or unsafe water and sanitation) to modern risks (e.g. overweight and obesity). Modern risks may take different trajectories in differen; 1.4Measuring impact of risk.